Contribution to the Banjul Multi-sectoral Integrated Livestock Management Resolution on transhumance in the Gambia - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
The Resolution aims to address the the social, ecological and resource stress caused by transhumance